Country-specific and individual determinants of dizziness in Europe: results from the Survey of Health Ageing and Retirement in Europe (SHARE). (August 2017) - Penger, M.; Strobl, R.; Grill, E.
Abstract: Objectives: Dizziness is one of the most common complaints amongst older persons and has relevant consequences for functioning. However, the epidemiological findings on dizziness are scarce and inconsistent and prevalence varies considerably among existing studies. Hence the objective of this study is to compare the prevalence of dizziness in persons aged 50 years or older across several European countries. The specific aim was to identify country- and person-specific determinants associated with a higher risk. Study design: Cross-sectional study. Methods: Data from the Survey of Health Ageing and Retirement in Europe project, covering 20 countries were analysed. Micro-data on more than 69, 000 persons aged 50+ years and additional macro-data on economic inequality, climate and urbanisation were included. We applied multilevel models to examine the impact of country-50 years or older specific determinants as well as individual characteristics on prevalence of dizziness. Results: We found a total of 12.4% of the participants in our sample were troubled by dizziness in the last 6 months. Prevalence ranged from 6.5% to 23.4%. In multilevel analysis several determinants on the country (higher proportion of urban population) and on the individual level (female gender, living alone, old age, poor education, presence of comorbidities, depressive symptoms, sensory problems, lack of physical activities) were identified. Conclusions: In conclusion dizziness is a common complaint amongst older Europeans that needs more attention. Further studies should investigate the prevalence, determinants and management of defined vestibular and non-vestibular causes of dizziness across Europe. Highlights: Dizziness is a common complaint among Europeans aged 50+ years. Prevalence varied according to region, was higher in women and increased with age. An increasing degree of urbanisation was associated with higher prevalence. Public health is called upon to raise awareness for dizziness in older populations.